2006
DOI: 10.1158/0008-5472.can-05-3905
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic and Clinical Responses after Vaccinations with Peptide-Pulsed Dendritic Cells in Metastatic Renal Cancer Patients

Abstract: A phase I trial was conducted to evaluate the feasibility, safety, and efficacy of a dendritic cell-based vaccination in patients with metastatic renal cell carcinoma (RCC). Autologous mature dendritic cells derived from peripheral blood monocytes were pulsed with the HLA-

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
142
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(145 citation statements)
references
References 35 publications
0
142
1
2
Order By: Relevance
“…Dendritic cell vaccines have been evaluated in phase I-III clinical trials for patients with various solid tumors such as melanoma, [18][19][20] prostate cancer, 21,22 renal cell carcinoma [23][24][25] and lymphoma. 26,27 Immunological and also clinical responses observed in these patients prompted researchers in the field to extend the concept of DC vaccination also to leukemia patients.…”
Section: Discussionmentioning
confidence: 99%
“…Dendritic cell vaccines have been evaluated in phase I-III clinical trials for patients with various solid tumors such as melanoma, [18][19][20] prostate cancer, 21,22 renal cell carcinoma [23][24][25] and lymphoma. 26,27 Immunological and also clinical responses observed in these patients prompted researchers in the field to extend the concept of DC vaccination also to leukemia patients.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, there have been several reports of two HLA-A2 binding peptides derived from the MUC1 protein [25][26][27]. MUC1-specific CTLs have also been induced in vivo after vaccination of breast, ovarian, and metastatic renal cancer patients with peptide-pulsed dendritic cells (DCs) [16,28,29]. However, these approaches have generated only modest and infrequent clinical responses.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Clinical trials revealed promising immunologic and anti-tumor responses of antigenloaded DCs administered as a vaccine against cancer. [19][20][21][22] In the context of myeloma, DC-based immunotherapy alone or in combination with other strategies may also represent an interesting treatment modality. 23,24 Thus, recent studies investigated the potential of bortezomib to enhance DC-mediated anti-tumor immunity.…”
Section: Introductionmentioning
confidence: 99%